ChemInform Abstract: Synthesis and Computation of Diastereomeric Phenanthroline—Quinine Ligands and Their Applicaton in Asymmetric Henry Reaction. Issue 16 (22nd April 2014) - Zhang, Lili; Wu, Hao; Yang, Zhongyue; Xu, Xiufang; Zhao, Haitao; Huang, Yaodong; Wang, Yongmei
Abstract A newly developed ligand consisting of phenanthroline and quinine in combination with copper is used as a chiral catalyst in the asymmetric Henry reaction giving products with good yields and high enantioselectivities.